Penerapan Strategi Poster Session Pada Materi Kerucut Siswa Kelas VIII SMPN 2 Ndona - Maria Fatima Mei; Maria Waldetrudis Lidi (JOURNAL OF SONGKE MATH, 2019)
The purpose of this study was to improve student learning outcomes using the Poster Session strategy. Based on observations made by researchers in class VIII before the study, it was found that the lack of activity of students and many students who had not achieved learning outcomes according to the minimal completeness criteria was 60. The reason is that students are not actively involved by the teacher in learning process. Efforts to solve this learning problem the author uses the Poster Session strategy. The level of success is viewed from 3 aspects, namely student learning completeness which is examined from the results of the cycle I and II tests, observation of teacher activities and student activities. Based on the results of the analysis after the implementation of the study, the researchers found that all student learning completeness in the first cycle was 48% and in the second cycle was 95% so there was an increase in student learning outcomes by 47%. Observers' observations on the activities of students in learning cycle I were 57% and in cycle II 90% so there was an increase of 33%. Observer observation results on the first cycle teacher activities were obtained at 52.62% and in the second cycle it was 94.78% so that an increase of 42.16%